Pengaruh Current Ratio dan Debt Ratio terhadap Return on Asset pada PT Unilever Indonesia Tbk Tahun 2014-2023 - Ainah Munawaroh; Mirza Anindya Pangestika (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
The purpose of this study is to determine and analyze the effect of Current Ratio (CR) and Debt to Asset Ratio (DAR), to Return on Asset (ROA) at PT. Unilever Indonesia Tbk. This research method is quantitative. The population and sample of this study are quarterly financial reports at PT Unilever Indonesia Tbk in 2014-2023. The data for this study are secondary data using the official website of PT Unilever Indonesia Tbk, namely www.unilever.co.id. The sample in this study has 40 financial reports taken using saturated sampling techniques. Data analysis in the study uses multiple linear regression analysis using the SPSS 22 application. The results of the study show that partially and simultaneously the Current Ratio and Debt to Asset Ratio variables have an effect on Return on Assets. With a determination coefficient value of adjusted R Square of 0.379. This shows that 37.9% of the Return on Asset variable can be explained by the Current Ratio and Debt to Asset Ratio variables.